How To Maintain Employee Job Satisfaction Through Organizational Trust, LMX, And Negative Workplace Gossip - Kuntardina, Ari; Adiputra, Eka; Rochmayanti, Dewi; Lestariningsih, Marsudi; Safii, Abdul Azis (Universitas Pendidikan Indonesia, 2025)
Employees with high job satisfaction will reduce the desire to leave the organization. Organizations try to retain high-potential employees by paying attention to variables that affect employee job satisfaction. Negative workplace gossip and LMX allegedly affect organizational trust and job satisfaction. Organizational trust may affect job satisfaction. Quantitative research with a total sample of 41 from educational institutions and electrical installation companies. Data analysis used Smart PLS. The results showed that negative workplace gossip had a negative and significant effect on organizational trust, LMX had a positive and significant effect on organizational trust. LMX has a positive and significant effect on Job satisfaction. However, negative workplace gossip and organizational trust have a negative and insignificant effect on job satisfaction. The results show that to retain potential employees, efforts are needed to increase employee job satisfaction. Companies can do this by paying attention to negative workplace gossip and improving LMX to increase organizational trust.